Analisis Determinan Kemiskinan Propinsi Nusa Tenggara Timur - Nalle, Frederic Winston; Seran, Sirilius; Bria, Fransiskus (Fakultas Ekonomi Universitas Samudra, 2022)
Various policy packages from the local government are currently being activated to reduce the spike in poverty rates in the Province of East Nusa Tenggara. This is because this province is still classified as the poorest province in Indonesia. Realizing this, the aim of this research is to find out the dominant factors that influence the high number of poor people in NTT Province. In an effort to answer research problems, the analytical tool used is panel data analysis where the number of analysis units or cross section data is all districts/cities in NTT Province as many as 22 districts while for time series data starting from 2018-2021. The results of data analysis show that either partially or simultaneously, each independent variable, namely economic growth, the human development index and also the number of residents has proven to have a significant influence on the number of poor people in NTT Province.